The immortal Hulk. Of hell and of death - Ewing, Al, 1977- (Marvel Worldwide, Inc., a subsidiary of Marvel Entertainment, LLC, 2021)
"We thought they were dead. We thought they'd been banished, controlled, made harmless. We were wrong. The gamma monsters are coming back--converging, one by one, on New York City. And who can stop them now? Who can save us... from the Immortal Hulk? The Avengers are ready to give it their best shot--but last time around, their battle against the Hulk was just business, and they destroyed an entire town. Now they're in the middle of New York City, about to take on a very different kind of Hulk... and it's become personal. Run for your lives!"--